2013
DOI: 10.1146/annurev-matsci-071312-121634
|View full text |Cite
|
Sign up to set email alerts
|

Flexoelectric Effect in Solids

Abstract: Piezoelectricity-the coupling between strain and electrical polarization, allowed 2 Zubko, Catalan, Tagantsev by symmetry in a restricted class of materials-is at the heart of many devices that permeate our daily life. Since its discovery in the 1880's by Pierre and Jacques Curie, the piezoelectric effect has found use in everything from submarine sonars to cigarette lighters. By contrast, flexoelectricity-the coupling between polarization and strain gradients, allowed by symmetry in all materials-was largely … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

23
713
1
12

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 883 publications
(749 citation statements)
references
References 135 publications
(135 reference statements)
23
713
1
12
Order By: Relevance
“…Meanwhile, generally, the mechanical boundary conditions should be modified as well [23,53]. The modified mechanical boundary conditions were recently derived by Yurkov [53] 12 . It has been shown that such a modification is not needed for the case where the polarization vanishes at the surface.…”
Section: General Casementioning
confidence: 99%
“…Meanwhile, generally, the mechanical boundary conditions should be modified as well [23,53]. The modified mechanical boundary conditions were recently derived by Yurkov [53] 12 . It has been shown that such a modification is not needed for the case where the polarization vanishes at the surface.…”
Section: General Casementioning
confidence: 99%
“…In particular, strain-engineering of multiferroism has opened a path for the exploration of new phases with improved properties compared to their bulk parents [10][11][12][13][14] Recently, the coupling between strain gradients and polarization, known as flexoelectricity 15 , has been analyzed intensely due to its remarkable contribution to the polarization and permittivity of inhomogeneously strained ferroelectrics [16][17][18][19][20][21] . The most dramatic manifestations of flexoelectricity have been reported in thin films, as it is an inherently size-dependent 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 5 phenomenon where strain gradients are inversely proportional to size 19,20,22 .…”
mentioning
confidence: 99%
“…This chapter introduces the fundamental physics and concepts of dielectrics [30][31][32][33][34][35][36][37][38][39] and their classification [38][39][40][41][42][43][44][45][46] , as well as of ferroelectrics 2,16,29,[37][38][39][40][41][42][43][44][45][46][47][48][49][50] , and relaxor ferroelectrics. [51][52][53][54][55][56][57] The information of many textbooks and review papers related to the physics of materials science was employed throughout these sections.…”
Section: Theoretical Backgroundmentioning
confidence: 99%